Story Mapping: An Effective Technique for Improving Students' Writing Ability at Middle School Students - Nuraini, Hani; Subari, Imam; Wahyuningsih, Sri (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2022)
This research aimed to improve the students’ writing skill of narrative text by using Story Mapping Technique. The researcher used Classroom Action Research as the design of collecting data. The subject of the research was held in one class with 34 students’. It consisted of 2 cycle, in collecting data the researcher used observation sheet and writing test. The research finding of the learning activities that were improvement from cycle 1 to cycle 2. The writer had the mean score in cycle 1 was 6.28, in cycle 2 obtained the mean score was 7.74. there were increased by 1.46. The result of writing test in cycle 1 that had the mean score was 57.11 but in cycle 2 the mean score was obtained 79.56, there were increased by 23.45. There were improvement of writing test from cycle 1 to cycle 2. The writer found the result of students’ completeness in cycle 1 was 41.18% and of the cycle 2 was 79,41% which active categorized. Therefore it can be concluded that the implementation of story mapping technique was successful to improve the students’ learning activities and students’ writing skill of narrative text at the class eighth of MTS. Raudhatul Mu’minin Bandar Lampung in Academic Year of 2021/2022.